Reproductive performance, inbreeding evolution, and genetic diversity of the Venezuelan Carora cattle evaluated through pedigree analysis - Cartuche-Macas, Luis F.; Perez-Gonzalez, José R.; Jimenez-Quintero, Ernesto J.; Gutiérrez-Reinoso, Miguel A.; Garcia-Flores, Joar; García-Herreros, Manuel (Frontiers in Veterinary Science, 2025)
The native Carora dairy breed was created in Venezuela with the objective of improving cattle adaptation to tropical conditions and increasing the production performance. The aim of this research was to study the reproductive performance, inbreeding evolution, and genetic diversity of the indigenous Carora breed using official pedigree information from the Carora Cattle Association of Venezuela. The total population included 72,411 females and 8,067 males. Six databases were considered: historical (all individuals born between 1985 and 2024 = 80,473), four populations born from 1985 to 2024 taken at 10-year intervals (1985–1994; 1995–2004; 2005–2014; 2015–2024) that included 8,442, 15,694, 34,987, and 21,350 individuals, and reference population (individuals with known sire and dam within of the population in the last period). Population structure variables were pedigree completeness index (PCI); number of equivalent (GEq), complete (GCom); and maximum (GMax) generations; and generation interval (GI). GD variables were inbreeding (F), inbreeding increment (ΔF), average relatedness (AR), co-ancestry (C), non-random mating (α), effective population size (Ne), and genetic conservation index (GCI). The gene origin probability variables were number of founders (f), effective number of founders (fe) and ancestors (fa), number of equivalent genomes (fg), fe/fa and fg/fa ratio, and GD losses. The databases were analyzed by ENDOG, POPREP, CFC, Re-laX2, and GRAIN v.2.2 software. PCI in the historical population compared to the population of the last period increased from 60.54 to 70.93% in the first generation, while the GI decreased from 5.78 to 5.95 years in the historical and last period, respectively. Moreover, F = 2.35%, AR = 4.04%, ΔF = 0.43%, C = 2.02%, α = 0.0034; GCI = 2.27, and Ne-Coan = 132.53 values were obtained in the last period. Gene origin probability in the reference population was fa = 28, fe = 58.69, fg = 27.74, fg/fe = 2.10, showing a GD loss due to unequal contribution of founders (0.85%) and bottleneck and genetic drift (0.95%). In conclusion, the native Carora cattle population displayed low-average genetic diversity, and its inbreeding value increased over time. Thus, conservation strategies, such as introducing new purebred bloodlines, establishing gene banks, and developing genetic improvement programs, would be crucial to minimize the future inbreeding to prevent the GD loss in native Carora cattle.